Building Health Policy and Systems Research (HPSR) capacity in India: Reflections from the India HPSR fellowship program (2020-2023) - Shilpa John; Sudha Ramani; Syed Mohd Abbas; Sumit Kane; Dorothy Lall; Prashanth N. Srinivas; Devaki Nambiar; Bruno Marchal; Sara Van Belle; Rajeev Sadanandan; Narayanan Devadasan (BMC, 2024)
Abstract Building capacity for Health Policy and Systems Research (HPSR) is critical for advancing the field in lower- and middle-income countries (LMICs). The India HPSR fellowship program is a home-grown capacity-building initiative, anchored at the Health Systems Transformation Platform (HSTP), New Delhi, and developed in collaboration with a network of institutes in India and abroad. In this practice-oriented commentary, we provide an overview of the fellowship program and critically reflect upon the learnings from working with three cohorts of fellows between 2020 and 2023. This commentary draws on routine program documentation (guidelines, faculty meeting reports, minutes of meetings of curricula and course development) as well as the perspectives of faculty and program managers associated with the fellowship. We have had several important learnings in the initial years of program implementation. One, it is important to iteratively modify globally available curricula and pedagogies on HPSR to suit country-specific requirements and include a strong component of 'unlearning' in such fellowships. Secondly, the goals of such fellowship programs need to be designed with country-specific contextual realities in mind. For instance, should publication of fellows' work be an intended goal, then contextual deterrents to publication such as article processing fees, language barriers and work-related obligations of faculty and participants need to be addressed. Furthermore, to improve the policy translation of fellows' work, such programs need to make broader efforts to strengthen research-policy-practice interfaces. Lastly, fellowship programs are cost-intensive, and outputs from them, such as papers or policy translation, are less immediate and less visible to donors. In the absence of these outputs, consistent funding can be a roadblock to sustaining these fellowships in LMICs. The experience of our fellowship program suggests that LMIC-led capacity-building initiatives on HPSR have the potential to influence changes in health systems and build the capacity of researchers to generate evidence for policy-making. The sharing of resources and teaching material through the fellowship can enable learning for all institutions involved. Furthermore, such initiatives can serve as a launchpad for the creation of regional and international HPSR communities of practice, with a focus on LMICs, thereby challenging epistemic injustice in teaching and learning HPSR.